MODERN SURGICAL TECHNOLOGIES IN THE TREATMENT OF MENINGEAL AND NEUROEPITHELIAL BRAIN TUMORS: A COMPARATIVE CLINICAL STUDY - Mamadaliev Abduraxmon Mamatkulovich (Research Focus International Scientific Journal, 2026)
Background. Surgical treatment remains the primary modality for meningeal and neuroepithelial brain tumors; however, traditional techniques are often associated with significant intraoperative blood loss, prolonged operative time, and a high risk of neurological deficits. Objective. To compare the outcomes of surgical treatment of meningeal and neuroepithelial brain tumors using standard techniques and modern technologies aimed at reducing surgical trauma. Materials and Methods. A retrospective analysis of 70 patients operated on for brain tumors was performed. Patients were divided into two groups: a comparison group treated with standard surgical methods and a main group treated using modern technologies, including ultrasonic disintegration, neuronavigation, intraoperative ultrasound, cortical mapping, and plasma-based coagulation. Intraoperative blood loss, duration of surgery, and safety of surgical access were assessed. Results. The use of modern technologies significantly reduced intraoperative blood loss and operative time compared with standard techniques (p < 0.05). Improved hemostasis reliability and safer surgical trajectories contributed to a lower risk of postoperative neurological deterioration. Conclusion. The integration of modern microsurgical, ultrasonic, and plasma technologies significantly improves the safety and efficiency of surgical treatment of meningeal and neuroepithelial brain tumors.